PENGARUH PERPUTARAN KAS, PERPUTARAN PIUTANG DAN PERPUTARAN PERSEDIAAN TERHADAP PROFITABILITAS (Study Pada Perusahaan Tekstil dan Garment Yang Terdaftar Di Bursa Efek Indonesia Periode 2014-2018) - Kamarudin Kamarudin; Uswatun Hasanah (Relawan Jurnal Indonesia, 2019)
This study aims (1) to determine the effect of cash turnover, accounts receivable turnover and inventory turnover partially effect on profitability (2) to determine the effect of cash turnover, accounts receivable turnover and inventory turnover simultaneously affect the profitability (3) to find out between cash turnover, accounts receivable turnover and inventory turnover are dominant influence on profitability. The method used is multiple linear regression analysis, t test, F test, dominant test and coefficient of determination. The results of the research are the multiple linear regression equation Y = 5,040 + 0,007X1 - 1,232X2 + 0,981X3 + e. T test for cash turnover (X1) tcount 0.203 <ttable 2.055 or sig α 0.841> 0.05 means that the cash turnover variable (X1) has no partial effect on the profitability variable. The value for the accounts receivable turnover variable (X2) -count -1.265> -table -2.055 or sig α 0.217> 0.05 means that the accounts receivable turnover variable (X2) has no partial effect on the profitability variable. The value for the inventory turnover variable (X3) tcount 2,300> t table 2.055 or sig α 0.030 <0.05 means that the inventory turnover variable (X3) partially influences the profitability variable. F test shows Fhitug 2,509 <Ftable 2.98 so that it can be concluded that cash turnover, accounts receivable turnover and inventory turnover have no simultaneous effect on profitability. The most influential dominant variable in this study is inventory turnover with a value of 2,300. Based on the coefficient of determination shows a value of 0.224 from these results means that all independent variables have a contribution of 22.4% to the dependent variable Profitability with a significant degree of determination, and the remaining 77.6% is influenced by other factors not included in the study.